Determinação do teor de biodiesel em suas misturas com diesel por cromatografia a gás - SANTOS, Iran Talis Viana (2015)
Biodiesel participates in the national energy matrix as an additive to mineral diesel. To control the proportion of biodiesel in the blend, the National Agency of Petroleum, Natural Gas, and Biofuels (ANP) established method EN-14078:2003, employing spectrometry in the mid infrared (IR-mid) region. In the method, the ester content in the fuel is determined indirectly through the absorption band of the grouping (C=O) present only in the biodiesel. The method is vulnerable to the identification of triacylglycerides from the vegetable oil and/or animal fat in nature, as the grouping (C=O) is also present in the mineral oil. Studies show that the physicochemical properties of the fuel are changed depending on the type and amount of biodiesel esters. Thus, these parameters should be monitored, as biodiesel is a function of the composition of the raw material used in its production, influencing the quality of the final product. In order to solve this problem, a primary analytical method employing chromatography using dimensional gas and a flame ionization detector (FID) for the direct determination of each type of ester in the fuel was developed, identifying the raw material source and content of esters present in the biodiesel in its mixtures with diesel oil. The developed method is free of oil or fat interference in nature. Therefore, it is possible to easily identify tampering or contamination with vegetable oil or animal fat in marketed fuel. It has been found that the method was effective in the separation, identification, and quantification of esters in B1 to B20 samples, and can be used as the primary method for analyzing national biodiesel.